Sirt3 Promotes Chondrogenesis, Chondrocyte Mitochondrial Respiration and the Development of High‐Fat Diet‐Induced Osteoarthritis in Mice. (27th October 2022) - Zhu, Shouan; Donovan, Elise L.; Makosa, Dawid; Mehta‐D'souza, Padmaja; Jopkiewicz, Anita; Batushansky, Albert; Cortassa, Dominic; Simmons, Aaron D.; Lopes, Erika Barboza Prado; Kinter, Michael; Griffin, Timothy M.
ABSTRACT: Understanding how obesity‐induced metabolic stress contributes to synovial joint tissue damage is difficult because of the complex role of metabolism in joint development, maintenance, and repair. Chondrocyte mitochondrial dysfunction is implicated in osteoarthritis (OA) pathology, which motivated us to study the mitochondrial deacetylase enzyme sirtuin 3 ( Sirt3 ). We hypothesized that combining high‐fat‐diet (HFD)‐induced obesity and cartilage Sirt3 loss at a young age would impair chondrocyte mitochondrial function, leading to cellular stress and accelerated OA. Instead, we unexpectedly found that depleting cartilage Sirt3 at 5 weeks of age using Sirt3‐flox and Acan ‐Cre ERT2 mice protected against the development of cartilage degeneration and synovial hyperplasia following 20 weeks of HFD. This protection was associated with increased cartilage glycolysis proteins and reduced mitochondrial fatty acid metabolism proteins. Seahorse‐based assays supported a mitochondrial‐to‐glycolytic shift in chondrocyte metabolism with Sirt3 deletion. Additional studies with primary murine juvenile chondrocytes under hypoxic and inflammatory conditions showed an increased expression of hypoxia‐inducible factor (HIF‐1) target genes with Sirt3 deletion. However, Sirt3 deletion impaired chondrogenesis using a murine bone marrow stem/stromal cell pellet model, suggesting a context‐dependent role of Sirt3 in cartilage homeostasis. Overall, our data indicate that Sirt3 coordinates HFD‐induced changes in mature chondrocyte metabolism that promote OA. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR). Abstract : Cartilage‐specific depletion of Sirt3 protects against osteoarthritis in adult mice fed a high‐fat diet, potentially by increasing chondrocyte glycolysis and inhibiting mitochondrial metabolism. However, Sirt3 deletion impairs chondrogenesis, suggesting a context‐dependent role of Sirt3 in cartilage homeostasis.